Validation of a 21-day, partial-mouth gingivitis model for evaluating chemotherapeutic dentifrices - Putt, M S; Van der Weijden, G A; Kleber, C J; Saxton, C A (Journal of periodontal research, 1993)
The experimental gingivitis model has long been used to evaluate chemotherapeutic agents in mouthrinses. Only recently however has the model been modified to test undiluted dentifrices by using a toothshield both to apply dentifrice and to protect selected teeth from toothbrushing. This also enables participants to brush the rest of the mouth and avoid the unpleasantness of 3 weeks without oral hygiene. Because of its well-documented efficacy, chlorhexidine was used in a toothpaste formulation to investigate the validity of the partial-mouth, experimental gingivitis model for evaluating therapeutic dentifrices. Optimal gingival health was established in 88 adults, who then were randomly assigned to two equal groups. A toothshield was constructed for each subject to fit the teeth of one mandibular quadrant. During the trial chlorhexidine or placebo dentifrice was applied undiluted to the test teeth via the toothshield, which also prevented plaque removal during brushing of the remaining dentition. After 21 days, plaque and gingivitis had developed in both groups. However, the chlorhexidine group had significantly less plaque and gingivitis than the placebo group. No adverse soft tissue effects were observed. This study demonstrated that the partial-mouth, experimental gingivitis model allowed unhindered development of plaque and gingivitis that was comparable to whole-mouth studies in which oral hygiene was suspended for 3 weeks. By corroborating with chlorhexidine, it is concluded that this short-term clinical model is valid for evaluating the chemotherapeutic effects of dentifrices.